Antioxidant, Mineralogenic and Osteogenic Activities of Spartina alterniflora and Salicornia fragilis Extracts Rich in Polyphenols - Roberto, Vânia P.; Surget, Gwladys; Le Lann, Klervi; Mira, Sara; Tarasco, Marco; Guérard, Fabienne; Poupart, Nathalie; Laizé, Vincent; Stiger-Pouvreau, Valérie; Cancela, M. Leonor (Frontiers in Nutrition, 2021)
Osteoporosis is an ageing-related disease and a worldwide health issue. Current therapeutics have failed to reduce the prevalence of osteoporosis in the human population, thus the discovery of compounds with bone anabolic properties that could be the basis of next generation drugs is a priority. Marine plants contain a wide range of bioactive compounds and the presence of osteoactive phytochemicals was investigated in two halophytes collected in Brittany (France): the invasive Spartina alterniflora and the native Salicornia fragilis. Two semi-purified fractions, prepared through liquid-liquid extraction, were assessed for phenolic and flavonoid contents, and for the presence of antioxidant, mineralogenic and osteogenic bioactivities. Ethyl acetate fraction (EAF) was rich in phenolic compounds and exhibited the highest antioxidant activity. While S. fragilis EAF only triggered a weak proliferative effect in vitro, S. alterniflora EAF potently induced extracellular matrix mineralization (7-fold at 250 g/mL). A strong in vivo osteogenic effect was also observed in vivo using zebrafish operculum assay (2.5-fold at 10 g/mL in 9-dpf larvae). Results indicate that polyphenol rich EAF of S. alterniflora has both antioxidant and bone anabolic activities. As an invasive species, this marine plant may represent a sustainable source of molecules for therapeutic applications in bone disorders.